A CORRELATION OF NON IONIC SURFACTANT CONCENTRATION, WATER SALINITY, AND OIL RECOVERY IN SANDSTONE IMBIBITIONS - Andry Prima; Sugiatmo Kasmungin (Prosiding Seminar Nasional Pakar, 2018)
The non ionic surfactant concentration is observed in a laboratorialexperiment in order to find its relations to the oil recovery. The integral part tothis study is the effect of water salinity on sandstone, which is used as coresample. In general, this experiment has proved the injection of non-ionicsurfactant concentration into the sandstone-core sample throughout theimbibitions linearly correlates to the oil recovery. Simultaneously, the studyfurther concludes that the Nonionic Surfactant Concentration workseffectively in low saline oil formation.